Designing community-based strategies to reach non-household contacts of people with tuberculosis in Lusaka, Zambia: a rapid qualitative study among key stakeholders - Kerkhoff, Andrew D.; Foloko, Marksman; Kundu-Ng’andu, Evelyn; Nyirenda, Herbert; Jabbie, Zainab; Syulikwa, Mainza; Mwamba, Chanda; Kagujje, Mary; Muyoyeta, Monde; Sharma, Anjali (Frontiers in Public Health, 2025)
BackgroundIn high-burden settings, most tuberculosis (TB) transmission likely occurs outside the home. Our qualitative study in Zambia explored the acceptability and preferences for designing TB active case finding (ACF) strategies to reach non-household contacts of people with TB.MethodsWe conducted 56 in-depth interviews with persons with TB (n = 12), TB healthcare workers (HCWs) (n = 10), TB lay HCWs (n = 10), and leaders/owners (n = 12) and attendees (n = 12) of community venue types identified as potential TB transmission locations. Interviews explored TB attitudes and beliefs, and perceptions toward two ACF strategies targeting non-household contacts: (1) “social-network strategy”—persons with newly diagnosed TB reach out to their close non-household contacts and (2) “venue-based strategy”—HCWs conduct screening at community venues frequented by persons with newly diagnosed TB. We used the Consolidated Framework for Implementation Research (CFIR) framework to develop interview topic guides and analyze data using a rapid deductive approach.ResultsAll participants felt that TB was an important issue in their community and that new detection strategies were needed. A “social-network strategy” was perceived as acceptable and feasible, where participants noted it was a caring act and could facilitate early diagnosis. For a “venue-based strategy,” most participants suspected TB transmission occurred at bars/taverns due to heavy alcohol use and prolonged time spent in crowded spaces; churches and betting halls were also commonly mentioned locations. Nearly all owners/leaders and patrons/attendees of bars, churches, and betting halls expressed acceptance of a venue-based strategy. They also indicated an interest in participating, citing many benefits, including increased TB knowledge/awareness, early diagnosis, convenience, and possibly reduced transmission, and recommended that the strategy incorporate sensitization, consent, volunteerism, and respectful, confidential, private services. For both strategies, most participants preferred the use of and being approached by trained peer TB survivors to facilitate ACF, given their prior TB patient experience and trust among community members.ConclusionStakeholders found social-network and venue-based TB-ACF strategies highly acceptable, recognizing their potential benefits for individuals and the broader community. Future research should evaluate the feasibility and effectiveness of TB ACF strategies for reaching non-household contacts.